METASOMATIC MANTLE BENEATH BARTOY VOLCANOES – THE ANCIENT CONTINENTAL MARGIN OR THE RECENT INTERACTION WITH THE HYDROUS PLUME MELTS? - Ashchepkov, I.V.; Ionov, D.A. (Ofioliti, 1999)
Bartoy volcanoes (Dzhida, Trans Baikal, 1.5-0.8 Ma) are located in the southern peripheral margin of the Trans Hamar Daban zone within the Miocene alkaline-basalt lava plateau. Abundant xenoliths are here found in every scoria cones. Petrography and chemistry of xenoliths and lavas vary between the sites. The youngest and most alkaline Krich Bolshoi volcano contains the most variable set of inclusions, including spinel lherzolites with mica or/and amphibole megacrysts, their intergrowths and various cumulates. Megacrysts are pyrope nodules (up to 20 cm) with rutile, Tiaugites rarely in intergrowth with Ti-biotite, kaersutites with the feldspars between grains; anorthoclases with inclusions of Ti-biotites and oxides; common ilmenite and Ti magnetite nodules and rare sapphires and zircons. Clinopyroxene megacrysts reveal also four or five temperature and compositional intervals, with the more Cr-rich varieties found in contact with peridotites. Different inclinations of trend lines in Fe- or T oC- Ti, Al, Na diagrams correspond to the changes of the associated phases from pyrope to phlogopite and probably alkali feldspar (see figure). Kaersutites that are more magnesian than augite megacrysts form the large veins with druses on the lherzolite walls and are the result of the AFC of the HT hydrous melts. The more ferriferous group continues the augite crystallization line further followed by Ti-biotites and Ti-magnetites with anorthoclases. This range of the megacrystalline assemblages reflects the T-P descending crystallization line in the chain of the connected vein-magma chamber system at the pre-eruption stage, which later served as the conductor for the erupted melts. The polymineral cumulates forming clusters of Cpx compositions on the T axes seem to be connected with the megacrystalline descending line being the apophyses from the main magmatic system. More Fe-rich Pl-Cpx-pyrope cumulates form two varieties: i) the HT coarse-grained; ii) the LT layered fine grained. The descending line of augite-pyrope cumulates with Phl and later Amph derived from the beginning of the Phl-augite group represent the thick veins in contact with the hydrated lherzolite. Special varieties of hydrous hybrid polymineral peridotites with magmatic mineral zoning likely result from low viscous melt percolation through the lherzolites. The green LT-MT Low-Cr cumulates sometimes with garnet were subjected to fracturing and metasomatism. The lherzolite metasomatic column is separated into intervals: 1) HT sheared Fe- lherzolites; 2) HT deformed porphyroclastic phlogopite lherzolite; 3) microvein intergranular phlogopite-amphibole lherzolite; 4) amphibole equi- and protogranular lherzolites and 5) protogranular anhydrous lherzolites. Na fluctuates within each group revealing two tendencies with descending T: 1) decrease (Jd) with pressure and 2) increase (Eug) with the intergranular differentiation. The K/Na ratio, Ti, F in amphiboles decrease together with the temperatures, which demonstrates the infiltration nature of metasomatism but Ba and Na increase what may suggest a preceding mantle wedge stage. In each group of metasomatics two (or three) modes of Na, Al, Ti depletion and Cr enrichment in minerals suggest hydration on the protolith. The bulk rock composition demonstrates Fe, Na, Ti growth in bottom (interaction) and top (differentiation and melt accumulation) of the mantle column. Two lower parts reveal the thermal excitation. The metasomatic minerals always reveal LREE-rich Gd/YbN>1 patterns which suggests derivation of fluids from OIB melts generated in garnet facies. The question is whether the hydrated mantle column results from the preceding mantle metasomatism later reactivated with the intruded plume magmas saturating in water when interacting with wall rocks or the initial juvenile water abundance produced the hydrous cumulative assemblages and peridotite hydration. The absence of hydrous cumulates in the earlier formed nearest volcanoes is in favour of the first assumption. But the Barun Hobol volcanic group, 15 km southward also contains phlogopite and pyrope as megacrysts. It is possible to suggest that the main magmatic chamber feeding all this volcanoes was located beneath the lithospheric mantle and produced a series of pulses with different saturation in water. One can suppose that they had the same feeding channels and the megacrysts were created not in a rising evolving system but as a succession of melt intrusions. Detailed comparison of the megacrysts from the nearest volcanoes will help solve this problem. The ore mineralization in Dzhida was produced by hydrous magmas generated from the Ordovician collision. The mineral isochrones for hydrous mantle lherzolites (Ionov et al., 1992) give also Paleozoic ages for the primary water enrichment of the Dzhida mantle domain. However nearest xenoliths localities in Hamar-Daban are anhydrous (Ashchepkov, 1991; Ionov et al., 1995). More likely the water saturation is a characteristic feature of the plume melts in peripheral regions with lower temperature and melt viscosity and presence of water in the deep protolith. Supported by RFBR grant (99-05-65688).